The national origins of policy ideas : knowledge regimes in the United States, France, Germany, and Denmark - Campbell, John L.; Pederson, Ove K. (Princeton University Press, 2014)
In politics, ideas matter. They provide the foundation for economic policymaking, which in turn shapes what is possible in domestic and international politics. Yet until now, little attention has been paid to how these ideas are produced and disseminated, and how this process varies between countries. The National Origins of Policy Ideas provides the first comparative analysis of how "knowledge regimes"--Communities of policy research organizations like think tanks, political party foundations, ad hoc commissions, and state research offices, and the institutions that govern them-generate ideas